Industrial Applications of Renewable Biomass Products : Past, Present and Future - Goyanes, Silvia Nair; D'Accorso, Norma Beatriz (Springer International Publishing : Imprint: Springer, 2017)
This book effectively links the latest scientific advances to current technological applications of polymers, mainly focusing on biodegradable polymers obtained from biomass. The individual chapters were written by academic and industry researchers alike, introducing readers to topics that have received little attention in the literature to date. Key topics covered include polymers used in various areas such as food packaging, pharmaceuticals, energy production and the cosmetics industry, as well as the treatment of aqueous effluents.